Optimization Production and Characterization of Bacterial Cellulose from Cornhusk - Widyastuti, Fikka Kartika; Kartika Fitri, Ayu Chandra (CHEESA: Chemical Engineering Research Articles, 2023)
Cornhusks are agricultural wastes with low economic value that will cause environmental pollution if not appropriately handled. Cornhusk waste can be processed as raw material for bacterial cellulose (nata) since it contains 44% cellulose. This study aims to optimize bacterial cellulose production from cornhusks and determine the effect of cornhusk mass and fermentation duration on the characteristics of the nata produced. The primary process for producing bacterial cellulose from cornhusks was fermentation by Acetobacter xylinum. The nata characterization carried out in this study includes thickness, yield, crude fiber, and moisture content, as well as statistical analysis to determine whether there was significant effect of variations in cornhusk mass and fermentation duration on bacterial cellulose production. Based on the results of optimizing the production of nata from cornhusks, the optimal mass of cornhusks was of 25 grams with fermentation duration of 17 days. Based on the characterization and data analysis results, variation on the cornhusks mass and duration of the fermentation had a significant effect on fiber content, yield, and tensile strength of bacterial cellulose from cornhusks. On the other hand, the variations on cornhusks mass and the duration of fermentation did not significantly affect the moisture content and thickness of bacterial cellulose from cornhusks.